1997
DOI: 10.1073/pnas.94.15.7915
|View full text |Cite
|
Sign up to set email alerts
|

The Xenopus proglucagon gene encodes novel GLP-1-like peptides with insulinotropic properties

Abstract: The proglucagon gene encodes several hormones that have key roles in the regulation of metabolism. In particular, glucagon-like peptide (GLP-1), a potent stimulus of insulin secretion, is being developed as a therapy for the treatment of non-insulin-dependent diabetes mellitus. To define structural moieties of the molecule that convey its insulinotropic activity, we have cloned and characterized the proglucagon gene from the amphibian, Xenopus laevis. Unexpectedly, these cDNAs were found to encode three unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 43 publications
1
59
0
Order By: Relevance
“…The second proglucagon gene encodes just glucagon and GLP-1 (figure 1b; Zhou and Irwin 2004). The structure of the frog proglucagon genes differs from the standard one, and these genes encode two or three GLP-1-like peptide sequences (Irwin et al 1997, Irwin andSivarajah 2000). Thus, although all vertebrates examined to date possess the hormones glucagon, GLP-1, and GLP-2, the structure of the genes that encode these hormones varies.…”
Section: Evolution Of Proglucagonmentioning
confidence: 99%
“…The second proglucagon gene encodes just glucagon and GLP-1 (figure 1b; Zhou and Irwin 2004). The structure of the frog proglucagon genes differs from the standard one, and these genes encode two or three GLP-1-like peptide sequences (Irwin et al 1997, Irwin andSivarajah 2000). Thus, although all vertebrates examined to date possess the hormones glucagon, GLP-1, and GLP-2, the structure of the genes that encode these hormones varies.…”
Section: Evolution Of Proglucagonmentioning
confidence: 99%
“…14 GLP-1R is expressed mainly by pancreatic beta-cells, and to some extent in other tissues (lungs, heart, kidney, GI tract and brain), and is coupled to the cyclic adenosine monophosphate (cAMP) second messenger pathway [14][15][16] involving activation of protein kinase A and the Epac family of cAMP-regulated guanine nucleotide exchange factors (cAMPGEFs). [17][18][19][20][21] Activation of other protein kinases including Akt (protein kinase B) and MAPK (mitogen-activated protein kinases 8,17,18 is also important in mediating GLP-1 action in promoting beta-cell growth and inhibiting apoptosis. GLP-1 enhances pancreatic islet beta-cell proliferation and inhibits beta-cell apoptosis in a glucose-dependent fashion.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the carp Cyprinus carpio suggest that allelic variability tends to increase after tetraploidization (Larhammar & Risinger 1994). Nucleotide sequence analysis of a cloned cDNA encoding preproglucagon-1 from X. laevis has shown that, after removal of the signal peptide, the precursor comprises 246 amino acids and contains the sequences of three peptides with structural similarity to GLP-1 (termed GLP-1A, GLP-1B, and GLP-1C) arranged in tandem, as well as sequences corresponding to mammalian glucagon and GLP-2 (Irwin et al 1997). In addition, the nucleotide sequence of a second Xenopus preproglucagon cDNA, encoding an identical glucagon but lacking the GLP-2 domain, has been deposited in the Gene Bank database (accession number AF004433·1) by the same investigators.…”
Section: Discussionmentioning
confidence: 99%
“…The techniques are applied to the clawed frog Xenopus laevis (Anura: Pipidae), a tetraploid organism for which the nucleotide sequences of cDNAs encoding two preproinsulins (Shuldiner et al 1989) and two preproglucagons (Irwin et al 1997) are known, and to the Japanese red-bellied newt Cynops pyrrhogaster (Caudata: Salamandridae), a diploid organism whose islet preprohormones have not been characterized at the nucleotide sequence level.…”
Section: Introductionmentioning
confidence: 99%